X‐ray fluorescence determination of major elements in ferromanganese nodules. (4th May 2020) - Chubarov, Victor; Amosova, Alena; Finkelshtein, Alexander
Abstract : In this article, the X‐ray fluorescence technique is proposed for the quantitative determination of major elements in ferromanganese nodules and crusts, which is a necessary stage of the oceanic ferromanganese deposits investigation and development. The research was performed using a wavelength‐dispersive spectrometer S4 Pioneer (Bruker AXS, Germany). Certified reference materials of ferromanganese nodules, cobalt‐bearing ferromanganese crusts and pelagic sediments were dried and prepared by two different techniques: the pressing of powder samples on a boric acid substrate and the homogenization by fusion with lithium tetraborate in an electric furnace at 1050°C. For each sample preparation technique, different forms of calibration curves (linear or quadratic) and methods of matrix effect correction (fundamental parameters or empirical intensities coefficients) were examined. The uncertainty of the proposed technique was assessed by analyzing the certified reference material FeMn‐1 and by comparison with the atomic absorption spectrometry, flame photometry and spectrophotometry results. Analysis of both fused beads and pressed pellets provides a quantitative determination of the major elements in the oceanic ferromanganese nodules.